The Effect of Gender and Music on Mathematic Skills Performance on Adult Population. - Afentouli Panagiota; Isaakidi Dimitra (2014)
Introduction, Methods, Results, DIscussion References, Appendix, Information Sheet, Consent Form, Demographic Questionnaire, Task Page 1, Task Page 2, Task Page 3, De-Brifing Sheet, SPSS - Results from Explore, SPSS Result from General Linear Model, References.